Chemical constituents from common vetch (Vicia sativa L.) and their antioxidant and cytotoxic activities. Issue 22 (16th November 2020) - Liu, Li-Fang; Li, Wen-Hai; Li, Man-Yu; Wu, Xiao-Zhen; Yang, Fan; Xu, Jia-Nan; Yuan, Cheng-Shan
Abstract: Vicia sativa L. (common vetch) is a potential food source for both human beings and animals because of its abundant nutritional composition. There is a lack of phytochemical study on the whole plant, and thus the objective of this study was to investigate the isolation of phytochemicals and evaluate their biological activities. A new flavanol, ( 2R, 3S )-3, 3′-dihydroxy-4′, 7-dimethoxyflavanol (1 ), together with nine known compounds, two flavones (2 –3 ), one coumarin (4 ), and six oleanane triterpenoids (5 –10 ), was obtained from Vicia sativa L.. The structure of the new compound 1 was determined via its NMR spectra, IR and CD data. Compound 3 displayed the potential of the DPPH (1, 1-diphenyl-2-picrylhydrazyl) radical scavenging effect in antioxidant test. In terms of cytotoxic activities, compound 3 showed moderate cytotoxic activities against three human tumor cells, especially HeLa cells. Graphical Abstract: